Editorial: Foster Care and Development - Daniela Reimer; Dirk Schäfer; Judith Pierlings; Klaus Wolf (Social Work & Society, 2017)
Foster Care Research in Europe is extremely diverse. Traditionally, it has been strongly informed by psychology, especially attachment theory, as well as by therapeutic initiatives and psychopathology. Furthermore, it has been influenced by ideological discussions about the status of foster families, with a varying emphasis on this in different countries (Cameron et al. 2015).